Application of a ROS / CoppeliaSim Integration in a Practical ”OBR” Competition Scenario - Joventino, Carlos Fernando; de Oliveira, André; Fabro, João Alberto; Pereira, Jonathas (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS); 2020: Anais do XII Simpósio Brasileiro de Robótica e XVII Simpósio Latino Americano de Robótica, 2020)
This work presents an integration of the CoppeliaSim robotics simulator together with ROS in a scene inspired by a stage in the practical modality of the Brazilian Robotics Olympics (OBR). A differential-type robot with 5 proximity sensors and 6 luminance sensors was used in the project. The dimensional characteristics of the robot and the position of the sensors, in addition to navigation control and obstacle avoidance strategies are presented throughout the work. The main objective is to allow students to understand the characteristics of the OBR challenges, and to study and interact with a robot in a simulated environment. The robot behavior is implemented using a PD (Proportional Derivative) controller for line-following, and a simple fuzzy controller for obstacle avoidance.